Relationship between Speed, Visibility, Resvonsiveness, Learning Orientation, Supply Chain Agility, Enviromental Dynamic, Competitive Agility and Covid-19 Pandemic (Case Study in UKM Labusel Region) - Salbiah Hasibuan; Sumitro Sarkum; Hayanuddin Sapri (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
The concept of supply chain agility is not very old, and a lot of research has been done to understand the constituents that build agility in operations and supply chains. As a continuation of that, this research contributes to the body of knowledge in many ways. First, make a theoretical contribution by exploring and explaining the factors that contribute to any supply chain agility especially in the context of the service industry in a volatile market. Second, in this study a framework is developed based on the dynamics of capability theory which is a big supporter of competitive agility by creating a value for H1: The results obtained with a value of Tcount 0.550 Ttable 0.098 at a significant level of 0.084 0.05. This means that the hypothesis can be accepted. H2: The results obtained with the value of Tcount 0.705 Ttable 0.098 at a significant level of 0.196 0.05. This means that the hypothesis can be accepted. H3: The results obtained with the value of Tcount 0.704 Ttable 0.098 at a significant level of 0.918 0.05. This means that the hypothesis can be accepted. H4: The results obtained with the value of Tcount 0.386 T table 0.098 at a significant level of 0.093 0.05. This means that the hypothesis can be accepted. H5: The results obtained with a Tcount value of 0.550 Ttable 0.098 at a significant level of 0.084 0.05. This means that the hypothesis can be accepted. H6: The results obtained with the value of Tcount 0.705 Ttable 0.098 at a significant level of 0.196 0.05. This means that the hypothesis can be accepted. Customers are uncommon and difficult to imitate and require effective organizational skills to be utilized efficiently and effectively. Third, by using SPSS 23, this study supports a causal relationship of factors that reduce agility as one of the abilities that organizations want to have. In addition, this study assigns weights among the factors that decrease agility where learning orientation explains agility the most, followed by speed, visibility, responsiveness, learning orientation and supply chain agility accordingly. Where speed has the highest explanation followed by appropriate visibility, responsiveness, orientation learning. However; more variables can be added to better understand supply chain agility and competitive agility.